Horse Theft in the Urals in the 1730s - Elena V. Borodina (Журнал Фронтирных Исследований, 2022)
The article is devoted to the problem of horse theft in the Urals in the 1730s. The main reason for this situation should be called the paucity of information about horse thieves, presented in the documents of the court and the investigation, which allow reconstructing the criminal world of early modern Russia. The author drew attention to the peculiarities of the region under study, which was a transit zone between the European and Asian parts of the Russian Empire and a major industrial center of the country. These features determined the special importance of horses not only in agriculture, but also in industrial production as a means of transporting goods and maintaining communication between the capital and the periphery. Analysis of the books of minutes of the Yekaterinburg Office of Judicial and Executive Affairs for the second half of the 1730s led to the conclusion that horse theft was widespread in the region. Most of those accused of stealing horses were residents who sought to escape from the difficult conditions of life in the Ural factories. At the same time, these sources allow us to conclude that there existed groups of horse thieves in the first third of the 18th c. in Russia, engaged in this business on a regular basis. Their thieving practices were similar to the activities of the organized groups of horse thieves in Russia in the second half of the 19th – early 20th centuries.